ALUMNI MANAGEMENT AND NETWORKING OF ISLAMIC EDUCATION INSTITUTIONS IN URBAN AREAS: A STUDY OF PESANTREN DARUNNAJAH JAKARTA AND PESANTREN DARUSSALAM GONTOR - Manaf, Sofwan; Kurniawan, Muhammad Irfanudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2024)
A strong philosophical foundation in the management of santri alumni management is expected to maintain the values that have been instilled during the education process in Pesantren when they are already in the community. However, modernity and reality in urban areas become a challenge for alumni in maintaining the religious character formed on traditional values in pesantren. The purpose of this article is to examine the implementation of the Panca Dharma and Panca Jiwa paradigms in the management of alumni and pesantren networks in urban areas. This research is a descriptive-analytical qualitative research using a case study approach. Primary data is in the form of observations and interviews with figures in the alumni management process at Pesantren Darunnajah and Pesantren Darussalam Gontor. While secondary data is in the form of written sources and scientific references including books, journal articles, theses, and theses related to the research topic. Data were collected using observation and interview methods and analysed using the content analysis method. The results showed that the principles of Panca Dharma and Panca Jiwa are formed on the emotional relationship between santri and kyai, which results in obedience and compliance. This is an effort of pesantren in maintaining religious santri in urban areas to remain in the frame of religious attitude inclusivism. Alumni's pride and appreciation for the pesantren can be seen from their awareness of worship and achievement in the community. Through a strong philosophical foundation, pesantren have succeeded in giving birth to thousands of alumni with various professions such as politicians, judges, businessmen, clerics and religious leaders with their pesantren, officials of state agencies, private sector, military and others. The orientation of pesantren education that prioritises society makes them more flexible in moving amid the dynamics of urban reality.